Evaluation of Seasonal Performance of Conventional and Phosphate‐Amended Biofilters. Issue 10 (1st October 2016) - Selbes, Meric; Amburgey, James; Peeler, Caleb; Alansari, Amir; Karanfil, Tanju
Abstract : A case study was conducted to evaluate the seasonal performance of conventional and phosphate‐amended biologically active filtration (BAF). Performance was evaluated in terms of general water quality parameters, disinfection by‐product (DBP) precursors, and operational parameters. BAF successfully reduced dissolved organic carbon and dissolved organic nitrogen by 3 to 36%, with higher reductions observed at warmer temperatures. The removal of the preceding two parameters corresponded to some decreases in trihalomethane, haloacetic acid, halonitromethane, and N ‐nitrosodimethylamine precursors. Phosphate amendment had some effect on water quality parameters, DBP precursors, and operational parameters. Phosphate amendment enhanced the microbial activity during cold‐temperature months, which resulted in higher particle counts compared with conventional BAF effluent. BAF can be an effective strategy for utilities to comply with disinfection by‐product regulations, especially in warm weather, and their amendment can further improve water quality and/or operation.